Extracorporeal Membrane Oxygenation as a Bridge to Durable Mechanical Circulatory Support: An Analysis of the STS-INTERMACS Database. (March 2020) - Loyaga-Rendon, Renzo Y.; Boeve, Theodore; Tallaj, Jose; Lee, Sangjin; Leacche, Marzia; Lotun, Kapildeo; Koehl, Devin A.; Cantor, Ryan S.; Kirklin, James K.; Acharya, Deepak
Abstract : Background: Limited data are available regarding the outcomes of patients supported by extracorporeal membrane oxygenation (ECMO) who undergo durable mechanical circulatory support implantation (dMCS). We analyzed the clinical characteristics, outcomes, and risk factors for mortality in patients who were bridged with ECMO to dMCS. Methods: Adult patients who received dMCS between January 2008 and December 2017 (n=19 824), registered in the Society of Thoracic Surgeons-Interagency Registry for Mechanical Assisted Circulatory Support (STS-INTERMACS) database were included. Baseline characteristics, outcomes, risk factors, and adverse events were compared between ECMO-supported patients (n=933) and INTERMACS profile 1 (IP-1) patients not supported by ECMO (n=2362). A propensity match analysis was performed. Results: ECMO patients had inferior survival at 12 months (66.1%) than non-ECMO patients (75.4%; P <0.0001). The proportion of patients transplanted at 2 years after dMCS was similar between the ECMO (30.8%) and non-ECMO (31.8%) groups ( P =0.49). A multiphase parametric hazard model identified 2 different periods based on risk of death. ECMO patients had a high hazard for death in the first 6 months after implantation (hazard ratio, 2.18 [1.79–2.66]; P <0.001). Multivariable analysis showed that ECMO was an independent risk factor associated with poor outcome during the early phase after dMCS (hazard ratio, 1.69 [1.37–2.09]; P <0.0001) but not during the constant phase. ECMO patients had similar outcomes to non-ECMO patients when a propensity matched cohort was analyzed. Conclusions: ECMO-supported patients before dMCS have lower survival compared with other IP-1 patients. A multivariable analysis showed that ECMO is an independent risk factor of poor outcome after dMCS. However, a propensity matched analysis suggested that when important clinical variables are controlled the outcome of both groups is similar. These data support the implantation of dMCS in carefully selected ECMO patients. Abstract : Supplemental Digital Content is available in the text.